Educational Studies on Historical Consciousness: Issues and Problems - Coudannes Aguirre, Mariela Alejandra (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2014)
This paper provides an overview of educational studies about historical consciousness. The route proposed is one among many possible and focuses specifically on the contributions to research in History Didactics in the last decades. This selection of European and American works (a view from South America) highlights the concern to clarify the factors influencing historical consciousness and the mechanisms for its construction. Also the role that the school may have in development of narratives that link past - present - future, without forgetting some problems and barriers in specific contexts. The latest research also implies that people itself should be assumed as actors who can change their reality, so that the relationship between the individual and the collective is one aspect to consider in the process of teaching and learning.